Bisnis, Pasar Bebas, dan Gereja - Mali, Mateus (Jurnal Orientasi Baru, 2015)
Our world now is economic world because it is colored by economic activities. Economic activities occur when two parties agree to the value or price of the transacted good or service, commonly expressed in a certain currency. A modern market is based on economy where goods and services are produced without interference and let the market run according to demand and supply. This article will deals with the John Locke’s concept about the economy, Adam Smith’s concept about the liberal economy, critic’s Karl Marx to the liberal economy, business and free market. The end of this article, I will present how the Catholic Church sees the economic activities as human activity for human development.